Negotiation : moving from conflict to agreement - Rockmann, Kevin W.; Langfred, Claus W.; Cronin, Matthew A. (Professor of management) (Los Angeles, CA : SAGE Publications, Inc., 2021)
Negotiation: Moving From Conflict to Agreement helps students see how negotiation is all around them. Using every day and business examples, authors Kevin W. Rockmann, Claus W. Langfred, and Matthew A. Cronin explain how to negotiate with an emphasis on when and why to use certain tactics and approach. Focusing on the psychology of negotiation levers such as reciprocity, uncertainty, power, and alternatives, the text helps students understand all the ways they can negotiate to create value. Packed with practical advice, integrated coverage of ethics, cases, and role-playing exercises, this compelling new text takes an applied approach to negotiation, allowing students to gain confidence and experience as they practice honing their own negotiation skills. Included with this title: The password-protected Instructor Resource Site (formally known as SAGE Edge) offers access to all text-specific resources, including a test bank and editable, chapter-specific PowerPoint® slides. Learn more.
Description based on XML content.
Keywords: Negotiation in business; Negotiation; Conflict management